Merintis TVET termaju: Rentas dunia rentas budaya - Kamalrudin, Massila; Suhaimin, Mohd Khairul Nizam (Penerbit UTeM Press, 2024)
Advanced Technical and Vocational Education and Training (TVET), a new generation educational and vocational education and training ( icon ) tool. TVET covers various aspects, including relevant curriculum, latest technology and partnerships with industry. "Pioneer of Advanced TVET, Across the World, Across Cultures' is a new book by Universiti Teknikal Malaysia Melaka.